Broad-spectrum tolerance to disinfectant-mediated bacterial killing due to mutation of the PheS aminoacyl tRNA synthetase - Miaomiao Chen; Runbo Cui; Shouqiang Hong; Weiwei Zhu; Qiong Yang; Jiahao Li; Zihan Nie; Xue Zhang; Yanghui Ye; Yunxin Xue; Dai Wang; Yuzhi Hong; et al. (Proceedings of the National Academy of Sciences, 2025)
Disinfectants are essential tools for controlling infectious diseases and maintaining sterile conditions in many medical and food-industry settings. Recent work revealed that a deficiency in the carbohydrate phosphotransferase system (PTS) confers pan-tolerance to killing by diverse disinfectant types through its interaction with the cAMP-CRP regulatory network. The present work characterized a pan-tolerance mutant obtained by enrichment using phenol as a lethal probe and an Escherichia coli PTS null mutant as a parental strain. The resulting super-pan-tolerant mutant, which harbored an F158C substitution in PheS, inhibited bacterial killing by multiple disinfectant classes with surprisingly little effect on antimicrobial lethality. The PheS substitution, which was expected to lower substrate recognition efficiency and result in deacylated tRNA phe occupying the ribosomal A site, activated relA expression and synthesis of ppGpp, even in the absence of disinfectant exposure. ppGpp, along with DksA, increased RpoS function by activating promoters of dsrA and iraP , two genes whose products increase the expression and stability of RpoS. Subsequently, RpoS upregulated the expression of genes encoding a universal stress protein (UspB) and an oxidative stress peroxidase (KatE), which preconditioned bacteria to better survive a variety of disinfectants. Disinfectant-mediated accumulation of reactive oxygen species (ROS) and bacterial killing were abolished/reduced by exogenous dimethyl sulfoxide and by a PheS F158C substitution up-regulating genes encoding ROS-detoxifying enzymes ( katE, sodA, oxyR, ahpC ). These data identify a pheS mutation-triggered, ppGpp-stimulated transcriptional regulatory cascade that negates biocide-mediated lethality, thereby tying the stringent response to protection from ROS-mediated biocide lethality.